Crystal structures of cefdinir, C14H13N5O5S2, and cefdinir sesquihydrate C14H13N5O5S2(H2O)1.5. Issue 3 (September 2019) - Wheatley, Austin M.; Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structures of cefdinir and cefdinir sesquihydrate have been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Cefdinir crystallizes in space group P21 (#4) with a = 5.35652(4), b = 19.85676(10), c = 7.57928(5) Å, β = 97.050(1) °, V = 800.061(6) Å 3, and Z = 2. Cefdinir sesquihydrate crystallizes in space group C2 (#5) with a = 23.98775(20), b = 5.01646(3), c = 15.92016(12) Å, β = 109.4470(8) °, V = 1806.438(16) Å 3, and Z = 4. The cefdinir molecules in the anhydrous crystal structure and sesquihydrate have very different conformations. The two conformations are similar in energy. The hydrogen bonding patterns are very different in the two structures, and the sesquihydrate is more stable than expected from the sum of the energies of cefdinir and cefdinir sesquihydrate, the result of additional hydrogen bonding. The powder patterns are included in the Powder Diffraction File™ as entries 00-066-1604 (cefdinir) and 00-066-1605 (cefdinir sesquihydrate).